Theories and applications of tea residue adsorbing aroma compounds: a review - Longjie Xu; Cunqiang Ma; Xuan Chen; Qizhen Du; Chuankui Song; Xinghui Li; Yong-Quan Xu (Beverage Plant Research)
Tea leaves have a good natural adsorption capacity due to their numerous pore structures and high specific surface area. Along with the advancement of tea process technology, more and more sites of adsorption and binding have been found in tea leaves, thus further improving the adsorption performance. Based on the original biological structure and internal components of tea leaves, the adsorption mechanism in tea leaves for exogenous compounds is mainly divided into physical adsorption theory and chemical adsorption theory. Compared with original tea leaves, modified tea leaves significantly improve adsorption performance with a specific adsorption function, which could improve the utilization rate of tea leaves and their waste residues. Techniques such as scanning electron microscopy provide basic data support for exploring the adsorption mechanism of tea leaves at the level of material structure and a theoretical basis for the development of specific adsorbents. Additionally, the application of thermodynamic adsorption models and adsorption kinetic equations could help to understand the process of tea adsorbing exogenous compounds and to visualize the adsorption process. The adsorption of exogenous additives by tea residue could make use of the affinity between functional groups. In future, these mechanisms will lay the foundation for its application in the field of substance adsorption and improve the utilization efficiency of renewable resources similar to tea leaves.